Time Perspective and Career Decision-Making Self-Efficacy: A Longitudinal Examination Among Young Adult Students - Kvasková, Lucia (2019)
This longitudinal study examined the relationship between Zimbardo time perspectives (TPs) and career decision-making self-efficacy (CDMSE). In total, 1,753 young adults participated in the longitudinal study. For the present study, we selected only participants who were students and provided information on TPs, CDMSE, and sociodemographic characteristics (n = 492, M = 22.97 years, SD = 1.32, 82.9% women). The results of multilevel modeling showed that future orientation and present-hedonistic TPs were positively related to CDMSE, whereas present-fatalistic and past-negative TPs were negatively related to CDMSE. These findings indicate that besides the beneficial effect of widely studied future TP, the negative role of past-negative and present-fatalistic TPs should be considered in connection with the career development of emerging adults.